Hematopoietic stem cell-derived exosomes promote hematopoietic differentiation of mouse embryonic stem cells in vitro via inhibiting the miR126/Notch1 pathway - LIAO Feng-ling; TAN Lin; LIU Hua; WANG Jin-ju; MA Xiao-tang; ZHAO Bin; CHEN Yanfang; BIHL Ji; YANG Yi; CHEN Riling (Acta Pharmacologica Sinica, 2018)
Abstract Cell-derived exosomes (EXs) can modulate target cell differentiation via microRNAs (miRs) that they carried. Previous studies have shown that miR126 is highly expressed in hematopoietic stem cells (HSCs) and plays a role in hematopoiesis via modulating the Notch pathway that participates in progenitors’ cell fate decisions. In this study we investigated whether HSC-derived EXs (HSCEXs) could affect the differentiation of mouse embryonic stem cells (ESCs) into HSCs. We prepared HSC-EXscon, HSC-EXssc and HSCEXsmiR126 from control HSCs and the HSCs transfected with scramble control or miR126 mimics, respectively. HSC-EXs were isolated by ultracentrifugation and analyzed using nanoparticle tracking analysis. We incubated the collected EXs with mouse ESCs over a 10-d differentiation induction period, during which HSC-EXs and a Notch pathway activator (Jagged1, 100 ng/mL) were added to the cultures every 3 d. After the 10-d differentiation period, the expression levels of miR126, SSEA1, CD117, Sca1, Notch1 and Hes1 in ESCs were assessed. The generated HSCs were validated by flow cytometry using antibodies against HSC markers (CD117, CD34 and Sca1). Our results revealed that: (1) transfection with miR126 mimics significantly increased miR126 levels in HSC-EXsmiR126. (2) HSC-EX co-culture promoted mouse ESCs differentiation into HSCs with the most prominent effect found in the HSC-EXsmiR126 co-culture. (3) HSC differentiation was verified by reduced SSEA1 expression and increased CD117 and Sca1 expression. (4) All the effects caused by HSCEXs were accompanied by significant reduction of Notch1 and Hes1 expression, thus inhibition of the Notch1/Hes1 pathway, whereas activation of Notch by Jagged1 abolished the effects of HSC-EXsmiR126. In conclusion, HSC-EXs promote hematopoietic differentiation of mouse ESCs in vitro by inhibiting the miR126/Notch1 pathway.